Coralie Reslinger, La diversité des modèles d’émergence technologique - Coralie Reslinger (Revue de la Régulation)
Emerging countries challenge the world economic hierarchy. It is above all their capabilities to upgrade within the global value chain which offers new insights and poses new questions to development economists. For this reason, we choose to study emergence into the technological prism.Different institutional systems have sustained technological emergence. In this thesis, we want to characterize the diversity of socio-economic models of technological upgrading in emerging countries. By adapting the Social Systems of Innovation and Production (SSIP) framework of Amable, Barré & Boyer (1997) for the study of 27 emerging countries in 2005, we analyse their institutional arrangements through six key domains (science and technology, education, international insertion, products, labour and financial markets) in order to observe the diversity of emerging models. We reveal the existence of five institutional architectures: cocktail, directed, de-centralised, finance-led and liberalised models. There is no world homogenisation even in an intense globalisation period because various institutional complementarities sustain these models. No optimal structure has to be adopted to enter into emergence. On the contrary, we show that, as institutional comparative advantages differ among this five emerging models, technological upgrading strategies have to be suitable. In this way, growth enhancing factors depend on national institutional architecture rather than on proximity to world technological frontier.